Major Challenges Facing Higher Education in the Arab World: Quality Assurance and Relevance 2019
DOI: 10.1007/978-3-030-03774-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Education Networks of Excellence Based on Quality, Accreditation, and Recognition Management: A Holistic Approach

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Three identifiers have been conceptualized: (1) mutual cultural appreciation; (2) institutional governmentality; and (3) quality control. Such triangle identifiers have been grounded in the focal case in this research, which is popularly cited in previous prestige pieces of literature of transnational education collaboration, for instance, culture issues [ 60 , 61 ], institutional structure [ 62 , 63 ], as well as the systematic process for high profile quality control [ 63 , 64 ]. The research findings for each of the identifiers is then further shown and elaborated in detail in the following sections.…”
Section: Research Findingsmentioning
confidence: 99%
“…Three identifiers have been conceptualized: (1) mutual cultural appreciation; (2) institutional governmentality; and (3) quality control. Such triangle identifiers have been grounded in the focal case in this research, which is popularly cited in previous prestige pieces of literature of transnational education collaboration, for instance, culture issues [ 60 , 61 ], institutional structure [ 62 , 63 ], as well as the systematic process for high profile quality control [ 63 , 64 ]. The research findings for each of the identifiers is then further shown and elaborated in detail in the following sections.…”
Section: Research Findingsmentioning
confidence: 99%
“…Vocational training is an example of how the Standard may expand standardized quality assurance beyond accreditation. Illustrative of the strong emphasis on alternatives to university education, the European Quality Assurance Framework for Vocational Education and Training (EQAVET) began as a project in 2019, VET21001, to provide tools and guidance for implementation of the Standard for vocational programs (EQAVET, n.d. For other types of HEIs, the new standard is recognized as the start of a cycle of change towards more standardized approaches to quality in higher education (Schumann et al, 2019). In the European context, ISO 21001 is seen as a potential tool to define the required quality assurance system of the Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG) (Anttila & Jussila, 2018).…”
Section: Eoms-a New Perspective On the Education Enterprisementioning
confidence: 99%